2022
DOI: 10.1007/s00394-022-02834-x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of dairy, meat, and fish intakes with risk of incident dementia and with cognitive performance: the Kuopio Ischaemic Heart Disease Risk Factor Study (KIHD)

Abstract: Purpose To investigate if dairy, meat, and fish intakes associate with dementia and cognitive performance. Methods We included 2497 dementia-free men from Eastern Finland, aged 42–60 years in 1984–1989 at the baseline examinations. Data on cognitive tests [Mini Mental State Exam (MMSE), trail making test (TMT), verbal fluency test (VFL), selective reminding test (SRT), and Russell’s adaptation of the visual reproduction test (VRT)] at the 4-year re-examina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 54 publications
(81 reference statements)
0
21
0
Order By: Relevance
“…The data in this study did not differentiate between types of meat or preparation methods, so it is possible that the protective effects of some meats and the detrimental effects of others counterbalanced each other to produce an insignificant finding. The insignificant findings of this study are unable to provide support for or against meat, but rather echo calls for further research to disentangle the complex relationship that different types of protein sources and preparation methods may have with dementia incidence (Ylilauri et al ., 2022)…”
Section: Methodsmentioning
confidence: 66%
See 1 more Smart Citation
“…The data in this study did not differentiate between types of meat or preparation methods, so it is possible that the protective effects of some meats and the detrimental effects of others counterbalanced each other to produce an insignificant finding. The insignificant findings of this study are unable to provide support for or against meat, but rather echo calls for further research to disentangle the complex relationship that different types of protein sources and preparation methods may have with dementia incidence (Ylilauri et al ., 2022)…”
Section: Methodsmentioning
confidence: 66%
“…Despite the appeal of a dietary strategy for reducing dementia incidence, research has yielded mixed results. Although prevailing dietary wisdom (Quan et al ., 2022) indicates that lowering meat consumption may be beneficial for dementia outcomes, this is not universally accepted with Ylilauri et al ., (2022) finding that there is no association between animal product consumption and dementia. Other studies have found protective effects of egg (Lee et al ., 2021), whole milk (Muñoz-Garach et al , 2021), and meat consumption (Ngabirano et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When we conducted a dose–response analysis of meat intake and the risk of NCI, five studies provided detailed data for ≥3 categories. 14,16,29,32,37 With the use of a restricted cubic splines model, we observed evidence of a linear association between fish and poultry intake and the risk of adverse cognitive outcomes ( p < 0.001; Fig. 6A and B).…”
Section: Resultsmentioning
confidence: 94%
“…Studies have considered that saturated fat and total cholesterol are risk factors for cardiovascular disease in relation to an increased risk of cognitive disorders. 14,29 However, adjusting those variables did not attenuate the association between meat consumption and cognitive disorders, which indicated that saturated fat and total cholesterol were not mediating factors. 15 Furthermore, in this study, the associations may be different if processed and unprocessed meats are studied separately; the consumption of unprocessed, lean meat may be favorable, whereas the consumption of processed meat is unfavorable; however, the findings are inconsistent.…”
Section: Food and Function Reviewmentioning
confidence: 96%
See 1 more Smart Citation